Implications of the Ketapang Religious Court Decision on Marriage Registration: Case Study at KUA Marau District - Bariyah, Oneng Nurul; Priyono, M. Rozi (MISYKAT AL-ANWAR JURNAL KAJIAN ISLAM DAN MASYARAKAT, 2026)
The background to this study relates to Case No. 6/Pdt.P/2020/PA.Ktp, concerning the judge‟s decision on the status of a guardian who married a woman in her capacity as guardian outside the provisions of the law. The purpose of this study is to analyse the implications of the Ketapang Religious Court‟s decision on the marriage validation of Case No.6/Pdt.P/2020/PA. Ktp on marriage registration. This study is a literature and field study. The approach taken by the author is descriptive qualitative. The data sources consist of primary and secondary data. Primary data was obtained through interviews with the Head of the Marau Subdistrict KUA and the panel of judges as well as the Chief Justice of the Ketapang Religious Court. Secondary data consists of the Ketapang Class IIB Religious Court Decision Directory, recordings and other documentation. The research concluded that, according to Islamic jurisprudence and the Compilation of Islamic Law, a non-Muslim guardian is invalid.